Comparative study of different cytotoxicity of bonding systems with different dentin thickness on L929 cell line: An experimental study - Ehsan Baradaran Nasseri; Ali Eskandarizadeh (Wolters Kluwer Medknow Publications, 2020)
Background: Dentin-bonding agents should have good biocompatibility as they come into close and prolonged contact with vital dentin. The present study aimed to evaluate and compare the cytotoxicity of total etch and self-etch dentin bonding systems with two different dentin thickness on L929 cell line. Materials and Methods: In this in vitro study 80 Class I cavities were prepared on the occlusal surfaces. The teeth were randomly divided to two groups of 40 each based on two RDT 0.5 mm and 1.5 mm. Samples were further subdivided into four subgroups of 10. Group 1: Adper Scotch bond Multi-Purpose (SBMP), Group 2: Adper Single Bond Plus (SBP), Group 3: Adper Scotch bond SE (SSE) and Group 4: Adper Easy One (EO). Group 1 and 2 were total-etch and Group 3 and 4 were self-etch. The cavities were sealed after applying of dentin bonding. Then crowns were immersed in culture medium for 24 hours and the cytotoxicity of resultant toxic extraction was measured with 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay in 4 serial dilutions (neat,1/2 ,1/10 ,1/100). Data were analyzed by Two-way ANOVA and t-test. Results: For all the dilutions, cytotoxicity was significantly higher with 0.5 mm remaining dentin thickness (RDT) relative to 1.5 mm RDT (P ≤ 0.05). In neat dilution for both RDTs, cytotoxicity was different among all the four dentin bondings. Expression in decreasing order of cytotoxicity was SBP > SBMP > SSE > EO for both RDTs in neat dilution (P < 0.05). For all the dilutions, cytotoxicity was significantly lower for self-etch bonding systems in comparison with total-etch bonding systems (P < 0.05). Conclusion: In the present study, lower cytotoxicity was found with an increase in the dilution of toxic extract and also cytotoxicity decreased with an increased dentin thickness. The adhesive systems had degrees of cytotoxic effects on cultured L929 compared to the control, except for the EO group.